1991
DOI: 10.1177/095646249100200411
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Syphilis: A Histopathological Study

Abstract: We present a study of biopsies taken from skin lesions of 44 patients presenting with primary or secondary syphilis. In most primary lesions erosion or, more often, ulceration was present, with a dense inflammatory infiltrate. In secondary syphilis a wide variety of histological changes was present. Blood vessels were frequently involved, with marked endothelial swelling and often proliferation. Treponemes were demonstrated with the Steiner staining method in all investigated cases of primary syphilis and in 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 7 publications
1
39
0
Order By: Relevance
“…Therefore, we tended to the diagnosis of a secondary syphilis in our patient. Plasma cells can be found in both syphilis stages 20 21. Serological findings did not aid in the decision for secondary or tertiary syphilis in this case.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, we tended to the diagnosis of a secondary syphilis in our patient. Plasma cells can be found in both syphilis stages 20 21. Serological findings did not aid in the decision for secondary or tertiary syphilis in this case.…”
Section: Discussionmentioning
confidence: 56%
“…Further, T. pallidum specifically attaches to vascular endothelium (37) and isolated basement membranes (22), and the organisms traverse endothelial cell monolayers by moving through the junctions between cells (20, 21, 31, 62, 68, 69). Additionally, two areas in which T. pallidum localizes include laminin-containing cutaneous nerves (65) and the dermal-epidermal junction within the perivascular area of the skin (5,15). Two interrelated hypotheses that can be drawn from these observations are that T. pallidum specifically localizes within infected tissues to areas rich in laminin and that the proximity of T. pallidum to perivascular locales during infection would arise from and facilitate treponemal dissemination via the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, they cause the tissue damage that ultimately gives rise to clinical manifestations, while on the other, they also are responsible for the clearance of treponemes, a prerequisite for lesion resolution (2,3). Cellular infiltrates composed of T lymphocytes, macrophages, and plasma cells are the sine qua non of syphilitic lesions (1)(2)(3)(4)(5)(6)(7). Immunocytochemical and RT-PCR analyses of early syphilitic skin lesions have revealed that these infiltrating cells, as well as keratinocytes and proximal vascular endothelium, are activated and that the T cells are elaborating cytokines consistent with a Th1 response (4,8).…”
Section: The Cutaneous Response In Humans Tomentioning
confidence: 99%